Ocenjevanje vpliva nekaterih dejavnikov in dejavnosti koroških dijakov na pojav nasilja v družini - Pogorevc, Jovita (Socialno delo, 2018)
In the first part, understanding of domestic violence within the framework of the Domestic Violence Prevention Act is presented, and later further expanded to other forms of domestic violence, such as intimate partner murders. Emotional violence is analysed in more details. Consequences of domestic violence are reviewed and legal basis for dealing with domestic violence is presented. Some risk factors that influence the occurrence of domestic violence, are presented, such as marital status, living environment, socio-economic situation and the number of children in the family. In the theoretical part, the correlation of the individual's views and the phenomenon of domestic violence is shown. In the second part, the results of a survey conducted among secondary school students of Slovenian Carinthia about their assessments of the impact of acts and factors on the occurrence of domestic violence are presented. The results show that students are more likely to deem as violent the direct acts (a slap, a threat, forcing into sexual intercourse, bullying, intimidation of a partner) rather than indirect ones (checking pockets, controlling financial resources, opening letters, verbal humiliation). Also, students assess alcohol as the most common factor affecting the onset of domestic violence, followed by illegal drugs, dissatisfaction with partner life, difficult childhood and problems at work.
Keywords: dijaki; nasilje v družini; nasilna dejanja; stališča